Risk factors associated with medium- to long-term outcome and health-related quality of life of patients with conservatively treated rib fractures - Benedikt Heyart; Cathleen Kmezik; Tobias Schöbel; Sebastian Krämer; Christian Kleber; Ulrich J. Spiegl (Scientific Reports)
Abstract Patients with rib fractures often suffer from prolonged pain and dyspnea. The purpose of this study was to evaluate the mid- and long-term outcomes and major predisposing risk factors for clinical limitations such as pain or reduced lung capacity in patients with conservatively managed rib fractures to provide a basis for optimizing current therapy. Patients who underwent conservative management of rib fractures between 2014 and 2018 at a level I trauma center were retrospectively reviewed. Inclusion criteria were Injury Severity Score (ISS) ≤ 16 points and a minimum follow-up of 3 years. Outcome parameters were the SF-36 physical and mental component summary score (PCS and MCS, respectively) as well as current pain and respiratory problems. Risk factors evaluated included age, body mass index (BMI), in-hospital days, number of rib fractures, fracture dislocation and serial rib fracture. PCS was comparable to the normal population. The correlation between age and PCS was significant, p = .002. BMI correlated significantly with PCS, p < .001, current pain, p = .034 and respiratory problems, p = .029. No significant correlations were observed for the number of rib fractures and in-hospital days. Fracture dislocation and serial rib fracture showed no effect on PCS, p = .134 and p = .914, respectively, and current pain, p = .916 and p = .357, respectively. In the medium- to long-term, conservative treatment of simple rib fractures or serial rib fractures showed good results, but was negatively affected by a high patient age or BMI.